Detection of atrial fibrillation and sinus pause in embolic stroke of undetermined sources by chest strap‐style 7‐day Holter monitoring. Issue 3 (17th March 2023) - Toi, Sono; Hosoya, Megumi; Ishizuka, Kentaro; Hoshino, Takao; Kitagawa, Kazuo
Abstract: Background: Long‐time monitoring of electrocardiogram with an implantable loop recorder is useful for detection of paroxysmal atrial fibrillation (PAF) in ESUS patients. However, usefulness of noninvasive 7‐day Holter monitoring has not been established. Furthermore, the incidence of other arrhythmias such as sinus pause (SP) remains unknown. Aim: (1) The aim of this study was to examine the usefulness of 7‐day Holter monitoring to detect PAF in both acute and chronic periods since index stroke and (2) to clarify the incidence of SP in ESUS patients. Methods: Prospectively, a total of 738 patients including 241 consecutive ESUS patients were enrolled, from April 2016 to March 2021. One hundred forty patients among 241 consecutive ESUS patients underwent chest strap‐style 7‐day Holter monitor. We examined PAF and SP (≧3 s). Results: The 7‐day Holter monitoring started since index stroke at a median of 17 days. Among 80 patients within 1 month since index stroke, PAF was detected in three patients (3.8%) and SP was in two patients (2.5%). By contrast, among 52 patients over 1 month since index stroke, PAF was found in only one patients (1.9%). Conclusion: Although the incidence of PAF detected with this monitoring was low (3.8%) in ESUS patients, SP was also found in 2.5% within 1 month since index stroke. Within 1 month since stroke onset in ESUS patients, 7‐day Holter monitoring would be useful for detection of PAF and SP that would be potentially a cardiac source of embolism and might require urgent intervention.